ROLE MODEL KEBIJAKAN PEMBERANTASAN PENYALAHGUNAAN NARKOTIKA DI KOTA PEKANBARU - Harirah MS, Zulfa; ', Isril (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Circulation and abuse of drugs in Pekanbaru city show significant improvement. Theefforts made by the National Narcotics Agency (BNN) in the field of prevention,empowerment, and the eradication has not been able to minimize the number of narcoticabuse in the city of Pekanbaru.Based on data from the Drug Investigation Division PoliceDirectorate Riau and Resta Pekanbaru, cases of drug abuse in Pekanbaru city in 2011 therewere 72 cases with 94 suspects, in 2012 there were 79 cases with 115 suspects, and in 2013as of October there were 102 cases with 129 suspects. Formulation of the problem in thisresearch ishow to role model appropriate policies in combating drug abuse in Pekanbaru city,so the purpose of this research is to find a role model of appropriate policies in combatingdrug abuse in the city of Pekanbaru and to the terms of role models of successfulimplementation of policies to eradicate drug abuse in the city of Pekanbaru.This research is aqualitative research with deskriptive method. This research was donethrough observation,in-depth interviews, Focus Group Discussion and documentation.Techniques of data analysis done by data reduction, organizing the data, and interpretation ofdata. The results of this research show that the efforts made by BNN Pekanbaru city ofprevention, empowerment, and eradication have not been able to minimize of drug abusecases in Pekanbaru city, although the value of the BNN gains of Pekanbaru city average in2012 is 107,5% and in 2013 is 118,34%. So as to minimize the abuse of drugs offered a rolemodel policies based on local wisdom that is returned to the Malay identity by means ofstrengthening traditional values of Malay culture and religious values.Keywords: Rolemodels, narcotics, policy, eradication